Analysis of Thermal and Physical (Mechanical) Properties of Local Fruits and Vegetables in Wukari, Taraba State, Nigeria - Onudibia Moses E.; Essiett Aniesua A.; Odoh Christopher M. , Iseh Amaitem J. , and (International Journal of Research in Informative Science Application & Techniques (IJRISAT), 2019)
In this research,physical methods have been used to analyzed fruits: black berry (Vitex Doriana), Shea butter (Vitellaria Paradixa), Bush Fig (Ficussur), Wild Custard Apple (Annona Senegalensis); Vegetables: Drumstick tree (Moringa oleifera), Zobo drink or Roselle (Hibiscus Sabdariffa) and Beans leave (Phaseolus vulgaris). The pH, density (ρ) , thermal conductivity (K), specific heat capacity (c), latent heat capacity (Lf ), thermal diffusivity (Td), moisture content( MC ), and the total solid (Ts ) were determined. The average mechanical properties of the samples are: pH (5.48), density (435.06Kg/m3), K (0.53JS m3), c (3.60J/kgK), Lhf (2585.61J/Kg), Td (3.89m2s-1), MC (76.77 %) and Ts is (23.25%). The following samples have the highest properties among others: Shea butter has pH (6.81), Wild Custard Apple has ρ (600Kg/M3), beans leave has K (0.5642 JS M3), beans leave has c (3.79J/kg K), beans leave has Lf (282840.00.J/kg), black berry Td (5.8802m2s-1), beans leave has Mc (84.43 %) and bush Fig has Ts (34.00%). The beans leave has the 50% highest property while other samples have the other 50% of the properties. The pH were acidic, K were lower than that of water, Td were higher than that of water, c and Lf were very high, the TS were high and MC were very high which make the sample perishable. To preserve these samples, their moisture contents have to be reduced. A lot of heat will be required to heat or cool these samples, because they are poor conductors of heat.